Photosynthetic performance of freshwater Rhodophyta in response to temperature, irradiance, pH and diurnal rhythm - Necchi Jr., Orlando [UNESP]; Zucchi, Marcelo Ribeiro [UNESP] (My University, 2001)
Responses of net photosynthetic rates to temperature, irradiance, pH/inorganic carbon and diurnal rhythm were analyzed in 15 populations of eight freshwater red algal species in culture and natural conditions. Photosynthetic rates were determined by oxygen concentration using the light and dark bottles technique. Parameters derived from the photosynthesis-irradiance curves indicated adaptation to low irradiance for all freshwater red algae tested, confirming that they tend to occur under low light regimes. Some degree of photoinhibition (β = -0.33-0.01 mg O2 g-1 DW h-1 (μmol photons m-2 s-1)-1) was found for all species/populations analyzed, whereas light compensation points (lc) were very low (≤ 2 μmol photons m- photons s-1) for most algae tested. Saturation points were low for all algae tested (lk = 6-54 μmol photons m-2 S-1; lS = 20-170 μmol photons m-2 s-1). Rates of net photosynthesis and dark respiration responded to the variation in temperature. Optimum temperature values for net photosynthesis were variable among species and populations so that best performances were observed under distinct temperature conditions (10, 15, 20 or 25°C). Rates of dark respiration exhibited an increasing trend with temperature, with highest values under 20-25°C. Results from pH experiments showed best photosynthetic performances under pH 8.5 or 6.5 for all but one species, indicating higher affinity for inorganic carbon as bicarbonate or indistinct use of bicarbonate and free carbon dioxide. Diurnal changes in photosynthetic rates revealed a general pattern for all algae tested, which was characterized by two relatively clear peaks, with some variations around it: a first (higher) during the morning (07.00-11.00 hours.) and a second (lower) in the afternoon (14.00-18.00 hours). Comparative data between the 'Chantransia' stage and the respective gametophyte for one Batrachospermum population revealed higher values (ca 2-times) in the latter, much lower than previously reported. The physiological role of the 'Chantransia' stage needs to be better analyzed.
Keywords: Diurnal rhythm; Freshwater Rhodophyta; Inorganic carbon; Irradiance; pH; Photosynthesis; Temperature; diurnal variation; irradiance; photosynthesis; red alga; temperature; algae; Batrachospermum; Chantransia; Eukaryota; Rhodophyta